Low Back Pain, Movement, and Posture. How do They Relate? - Wernli, Kevin (Curtin University, 2021)
This thesis investigated how movement, posture, and psychological factors change as people with back pain improve. Contrary to existing literature, we found that movement and posture changes were frequently related to pain and activity limitation changes, when research methods accommodated which movement or postures were clinically relevant for each person. Also, contrary to common beliefs, movement and posture consistently became less protective when related to improvement, with changes in psychological factors playing an important role.